Gorlin Syndrome, Vulvar Basal Cell Carcinomas, Vismodegib, and Lichen Sclerosus: From the ISSVD Case Consultation Committee. Issue 3 (July 2016) - Kirkpatrick, Emily; Dobriansky, Dwina; Scurry, James
Abstract : Lichen sclerosus developed, while vismodegib successfully treated vulvar basal cell carcinomas (BCCs) in Gorlin syndrome.